Phylogeny of tribe Dacini revisited (Diptera: Tephritidae: Dacinae) - Hancock, D.l.; Drew, R.a.i. (Zootaxa, 2024)
Phylogenetic relationships within the Dacini are discussed, with Dacimita David & Hancock and Ichneumonopsis Hardy transferred from tribe Gastrozonini to tribe Dacini based on synapomorphies and regarded as sister taxa to Monacrostichus Bezzi and Dacus Fabricius + Bactrocera Macquart respectively. The Madagascan genus Tythocalama Munro is removed from synonymy with subgenus Dacus (Neodacus) Perkins and placed as a new synonym of subgenus Dacus (Mictodacus) Munro.